Control of differentiation of a mammary cell line by lipids. - Dulbecco, R (1980)
A rat mammary cell line (LA7) undergoes spontaneous differentiation into domes due to production of specific inducers by the cells. Some of these inducers may be lipids, and we show that lipids regulate this differentiation as both inducers and inhibitors. One inhibitor is the tumor promoter tetradecanoyl-13 phorbol 12-acetate. The inducers are saturated fatty acids of two groups: butyric acid and acids with chain lengths from C13 to C16, especially myristic acid (C14). Other inducers are myristoyl and palmitoyl lysolecithins, myristic acid methyl ester, and two cationic detergents with a tetradecenyl chain. We propose that the lipids with a C14-C16 alkyl chain affect differentiation by recognition specific receptors through their alkyl chains and that the effects obtained depend on the head groups. These lipids may be physiological regulators in the mammary gland.